Externally bonded reinforcement side extended (EBRSE) technique to postpone debonding of FRP laminates in strengthened concrete elements - Mehdi Aghabagloo; Laura Carreras; Cristina Barris; Alba Codina; Marta Baena (Case Studies in Construction Materials, 2025)
Structural repair and strengthening have always been challenging tasks in construction. One of the most commonly applied techniques for Reinforced Concrete (RC) structures is the Externally Bonded Reinforcement (EBR). However, a persistent challenge with EBR is the premature debonding of FRP laminates from the concrete surface. In response, researchers have explored alternative techniques to improve this issue, leading to techniques such as Near-Surface Mounted (NSM) reinforcement, Externally Bonded Reinforcement on Grooves (EBROG), Externally Bonded Reinforcement in Grooves (EBRIG), and the use of mechanical fasteners. This study introduces and evaluates a new strengthening technique designed to enhance the conventional EBR approach while requiring minimal alterations to surface preparation, saving both time and costs. The proposed technique, presented as Externally Bonded Reinforcement Side Extended (EBRSE), involves applying resin to both lateral sides of the precured laminate parallel to the loading direction. In this work, single shear tests were conducted on concrete specimens using both EBRSE and conventional EBR techniques to compare their performance. Additionally, a numerical approach was applied, combining the finite difference method with a metaheuristic optimization algorithm, to derive the bond-slip law governing the constitutive behavior of both systems. The findings revealed that the EBRSE technique significantly outperformed the conventional EBR method, with an increase of up to 80 % in ultimate load capacity and up to 86 % in ultimate slip. Furthermore, the comparison between numerical predictions and experimental findings, specifically in terms of bond-slip law, load-slip curves, and strain distribution along the bonded FRP, confirmed an increase in fracture energy for the EBRSE technique.